Dinamika Mikroba dan Perubahan NPK Selama Fermentasi POC Kotoran Kambing - Syafira, Fira; Putri, Santi Diana; Fevria, Resti; Larashinda, Mentari (UNIVERSITAS LABUHANBATU, 2026)
The use of livestock waste as liquid organic fertilizer (LOF) is a sustainable solution for reducing dependence on chemical fertilizers and improving environmental quality. Goat manure has potential as a raw material for LOF because it contains the macronutrients nitrogen (N), phosphorus (P), and potassium (K), as well as microorganisms that play a role in the decomposition process. This study aims to analyze the dynamics of the microbial population (bacteria and fungi), changes in NPK nutrient content, and environmental conditions during the fermentation of goat manure POC. The study was conducted over 21 days at the Biology Laboratory of the Department of Agroindustry, University of Padang, using a completely randomized design with eight fermentation time points and three replicates. Microbial populations were analyzed using the Total Plate Count (TPC) method, while NPK content was measured using a Rapid NPK tester. Data were analyzed using ANOVA and the DMRT post-hoc test at the 5% level. The results showed that fermentation duration had a highly significant effect on microbial population and nutrient content. Bacterial population peaked on day 18, while fungal population was highest on day 15 of fermentation. The highest nitrogen content was obtained on day 21, while phosphorus and potassium were highest from days 18 to 21. The pH value remained relatively stable within the neutral range, and the temperature remained within the mesophilic range, which supports microbial activity. It was concluded that fermentation for 18–21 days produced POC with optimal biological and chemical quality and has the potential to be used as an environmentally friendly liquid organic fertilizer. Keywords: liquid organic fertilizer, goat manure, fermentation, microorganisms, NPK